ANALISIS IMPLEMENTASI KEBIJAKAN PELIMPAHAN SEBAGIAN KEWENANGAN BUPATI KEPADA CAMAT DALAM MENINGKATKAN PELAYANAN PUBLIK DI KECAMATAN BALARAJA - Trio, Anugerah Adi; Hartoko, Gatot; Saepudin, Eli Apud (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The delegation of some of the regent’s authority to the sub-district head was carried out to accelerate and facilitate public services to the community. However, in Balaraja Sub-district, problems such as slow service, lack of facilities, and minimal understanding of new tasks among officials were still found. This shows that the implementation of the policy has not been optimal as expected by the community. This study aims to determine how the policy of authority delegation is implemented in Balaraja Subdistrict, as well as the obstacles and impacts on public services. The method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The researcher uses Edward III’s theory, which covers communication, resources, implementer attitudes, and bureaucratic structure. The results show that this policy helps bring services closer to the community, but there are still many challenges. Some of the obstacles found include a lack of competent personnel, uneven communication, and suboptimal use of technology. The conclusion of this study is that there is a need to increase employee capacity, utilize digital technology, and supervise services so that the policy of delegating authority can run better and increase public satisfaction.